Changing behaviour of self help group members: Pathway for sustainable rural livelihoods in Eastern India - MEENA, M S; SINGH, K M (The Indian Journal of Agricultural Sciences, 2026)
The study evaluates the behaviour construct of self help group (SHG) members. Data were solicited from randomly selected 100 SHG members of Patna district, Bihar, India at two point of time (in before and after situation), i e during 2008 and 2013. The behaviour construct developed, consisted of 30 items, for which Cronbach’s alpha coefficient of reliability was observed as 0.82. Data were solicited on three-point continuum, viz. No Change=1, Slightly Changed=2 and Highly Changed=3. The mean values of two situations (before and after situation) were compared (z-statistics) to observe the behavioural change among the SHG members. An improvement of 34.91% between pre (46.09%) and post evaluation (81%) and a significant improvement in behaviour of SHG members was observed, which exemplifies the impact of SHG approach in instilling a positive behavioural orientation. Positive behaviour could play a great role in tackling the issues of rural poverty for improving sustainable livelihood security in eastern India. To achieve this rural livelihoods must assimilate the vital facets like (i) formation and stabilization of SHGs, (ii) pro-poor financial and credit support system, (iii) market-driven and decentralized extension system, (iv) diversification towards high-value enterprises, (v) technological intervention and impact assessment, (vi) media-mix for technology transfer, (vii) frequent educational tour/visits and interaction with other SHGs and research institutes, (viii) developing leadership skills, and (ix) strong political will. Nevertheless, extension system needs to be re-oriented and revitalized with new agricultural knowledge base in emerging technologies and methodologies.